RIGHT TO EQUALITY VIS-À-VIS RESERVATION POLICY AS PER SOCIAL SETUP IN INDIAN CONSTITUTION - Singh, Jobanjit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India became a Republic in 1950. The Preamble and Directive Principles of the Constitution envisage building a social order around the principles of equality, liberty, and fraternity. The intervention of the State in social transformation for an egalitarian and secular social order is the core and the spirit of the constitution. Keeping this core spirit at heart various articles have been embodied in the Constitution which inter alia covers provisions relating to reservation initially for the Scheduled Castes and Scheduled Tribes, Backward Castes, and Economically Weaker Section (EWS) of the Society.